Foliar resistance to Rhizoctonia solani in Arabidopsis is compromised by simultaneous loss of ethylene, jasmonate and PEN2 mediated defense pathways - Brendan N. Kidd (Nature Portfolio, 2021)
Abstract Rhizoctonia solani causes damaging yield losses on most major food crops. R. solani isolates belonging to anastomosis group 8 (AG8) are soil-borne, root-infecting pathogens with a broad host range. AG8 isolates can cause disease on wheat, canola and legumes, however Arabidopsis thaliana is heretofore thought to possess non-host resistance as A. thaliana ecotypes, including the reference strain Col-0, are resistant to AG8 infection. Using a mitochondria-targeted redox sensor (mt-roGFP2) and cell death staining, we demonstrate that both AG8 and a host isolate (AG2-1) of R. solani are able to infect A. thaliana roots. Above ground tissue of A. thaliana was found to be resistant to AG8 but not AG2. Genetic analysis revealed that ethylene, jasmonate and PENETRATION2-mediated defense pathways work together to provide resistance to AG8 in the leaves which subsequently enable tolerance of root infections. Overall, we demonstrate a significant difference in defense capabilities of above and below ground tissue in providing resistance to R. solani AG8 in Arabidopsis.